Riclinoctaose Attenuates Renal Ischemia-Reperfusion Injury by the Regulation of Macrophage Polarization - Zhao, Yang; Ding, Zhao; Ge, Wenhao; Liu, Junhao; Xu, Xi; Cheng, Rui; Zhang, Jianfa (Frontiers in Pharmacology, 2021)
Renal ischemia-reperfusion injury is a major trigger of acute kidney injury and leads to permanent renal impairment, and effective therapies remain unresolved. Riclinoctaose is an immunomodulatory octasaccharide composed of glucose and galactose monomers. Here we investigated whether riclinoctaose protects against renal ischemia-reperfusion injury. In mice, pretreatment with riclinoctaose significantly improved renal function, structure, and the inflammatory response after renal ischemia-reperfusion. Flow cytometry analysis revealed that riclinoctaose inhibited ischemia-reperfusion-induced M1 macrophage polarization and facilitated M2 macrophage recruitment into the kidneys. In isolated mouse bone marrow-derived macrophages, pretreatment with riclinoctaose promoted the macrophage polarization toward M2-like phenotype. The inhibitor of Nrf-2/HO-1 brusatol diminished the effects of riclinoctaose on macrophage polarization. In mice, intravenous injection with riclinoctaose-pretreated bone marrow-derived macrophages also protected against renal ischemia-reperfusion injury. Fluorescence-labeled riclinoctaose specifically bound to the membrane of macrophages. Interfering with mDC-SIGN blocked the riclinoctaose function on M2 polarization of macrophages, consequently impairing the renoprotective effect of riclinoctaose. Our results revealed that riclinoctaose is a potential therapeutic agent in preventing renal ischemia-reperfusion injury.